Transactions on aspect-oriented software development VIII - Katz, Shmuel; Mezini, Mira.; Schwanninger, Christine; Joosen, Wouter; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume, the 8th in the Transactions on Aspect-Oriented Software Development series, contains two regular submissions and a special section, consisting of five papers, on the industrial applications of aspect technology. The regular papers describe a framework for constructing aspect weavers, and patterns for reusable aspects. The special section begins with an invited contribution on how AspectJ is making its way from an exciting new hype topic to a valuable technology in enterprise computing. The remaining four papers each cover different industrial applications of aspect technology, which include a telecommunication platform, a framework for embedding user assistance in independently developed applications, a platform for digital publishing, and a framework for program code analysis and manipulation.
A Model-Driven Framework for Aspect Weaver Construction -- A System of Patterns for Reusable Aspect Libraries -- A Real-World Perspective of AOP -- Tackling the Challenges of Integrating 3rd Party Software Using AspectJ -- Puma: An Aspect-Oriented Code Analysis and Manipulation Framework for C and C++ -- Building a Digital Publishing Platform Using AOSD: Experiences and Lessons Learned.-An Aspect-Oriented Tool Framework for Developing Process-Sensitive Embedded User Assistance Systems.
Electronic reproduction.
Keywords: Electronic books; Computer science; Software engineering; Logic design; Computer simulation; Information Systems